Assessment of repurposed compounds against coronaviruses highlights the antiviral broad-spectrum activity of host-targeting iminosugars and confirms the activity of potent directly acting antivirals - Brun, J; Arman, BY; Hill, ML; Kiappes, JL; Alonzi, DS; Makower, LL; Witt, KD; Gileadi, C; Rangel, V; Dwek, RA; Von Delft, A; Zitzmann, N (Elsevier, 2025)
The COVID-19 pandemic highlights the need for novel antiviral drug discovery approaches that could dramatically shorten timelines from compound discovery to clinical development. At the beginning of the pandemic, repurposing approaches were at the forefront of early research efforts to screen for antiviral activity against SARS-CoV-2 in over 2,500 compounds. Here, we report cellular screening results of 100 FDA-approved and experimental compounds against SARS-CoV-2 in the human Calu-3 cell line. We observed 13 compounds showing antiviral activity against SARS-CoV-2, including seven FDA-approved compounds (remdesivir, boceprevir, amiloride, nafamostat, cisplatin, silmitasertib, and miglustat), and six compounds in pre-clinical and clinical development (tarloxotinib, lucerastat (NB-DGJ), MON-DNJ, NAP-DNJ, NN-DGJ and NN-DNJ). Further, we observed that our screening hits include several host-targeting antivirals, namely iminosugars, that are largely non-toxic and offer a large therapeutic window. The most-developed iminosugar MON-DNJ (UV-4B), which has been evaluated in a Phase 1 clinical trial, showed antiviral activity against SARS-CoV-2 wild type as well as alpha, beta, gamma, delta, and omicron variants. Its activity also extended to another betacoronavirus HCoV OC43, but not alphacoronavirus HCoV 229E. Our cellular screening results add to the body of knowledge on antivirals against coronaviruses and confirm the antiviral efficacy of iminosugars in cellular assays using the human lung-cell line Calu-3.